Dissociating arabic numeral reading and basic calculation: a case study. - García-Orza J; León-Carrión J; Vega O (Neurocase (Taylor & Francis Ltd), 2003)
This study is about JS, a patient who suffered from anomia, phonological dyslexia and severe writing problems following a left hemispheric stroke. He showed good arabic numeral comprehension as evidenced in number-comparison tasks, but impairment in transcoding arabic numerals into verbal numbers and verbal numbers into arabic numerals. Although JS had several operand reading errors, the four arithmetic operations were not affected. In calculations with arabic numerals, he produced the correct results both in oral and written responses. For instance, when presented with the multiplication '7 x 3', JS read the operation as 'four times five', but provided the correct response orally 'twenty one' and written '21'. This behavior goes against those hypotheses which posit that multiplication facts are verbally-based, and those which establish the same route for verbal number production in calculation and arabic numeral reading.